ASEAN RESPONSIBILITY TOWARD HUMAN TRAFFICKING VICTIMS UNDER THE ACTIP - Eva Arief; Sri Wulandari (Universitas 17 Agustus 1945 Semarang, 2026)
Human trafficking is a transnational crime that threatens human rights and has serious consequences for victims and regional stability. The high vulnerability of Southeast Asia to human trafficking has prompted ASEAN Member States to adopt the ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP) as a regional legal instrument to prevent and combat trafficking in persons and to protect its victims. This study aims to analyze ASEAN’s responsibility toward human trafficking victims under the ACTIP and to identify the challenges in its implementation. This study employs normative legal research using a statute approach and a conceptual approach. Legal materials were obtained through library research, including primary, secondary, and tertiary legal materials, and were analyzed qualitatively using a descriptive-analytical method. The findings demonstrate that ASEAN’s responsibility under the ACTIP is manifested through strengthened regional cooperation in preventing human trafficking, protecting and restoring victims’ rights, ensuring access to justice, and coordinating cross-border law enforcement. However, the effective implementation of these responsibilities continues to face several challenges, including differences in institutional capacity among Member States, the lack of uniform victim protection standards, weak mechanisms for monitoring ACTIP implementation, and the limited authority of ASEAN due to the principle of non-interference. Therefore, strengthening regional coordination mechanisms, harmonizing victim protection policies, and enhancing the effectiveness of ACTIP implementation are necessary to ensure more effective protection for human trafficking victims across the ASEAN region.